Correction: Mechanistic details of the cobalt-mediated dehydrogenative dimerization of aminoquinoline-directed benzamides. Issue 29 (16th July 2021) - Xu, Li-Ping; Liu, Elaine E. L.-N.; Bacsa, John; Ajitha, Manjaly J.; MacBeth, Cora E.; Musaev, Djamaladdin G.
Abstract : Correction for 'Mechanistic details of the cobalt-mediated dehydrogenative dimerization of aminoquinoline-directed benzamides' by Li-Ping Xu et al., Chem. Sci., 2020, 11, 6085–6096, DOI: ; 10.1039/D0SC02066D .